Economic Impact of Targeted Government Responses to COVID-19: Evidence from the First Large-scale Cluster in Seoul - Jinwook Shin; Seonghoon Kim; Kanghyock Koh (Institute of Labor Economics (IZA), 2020)
We estimate the economic impact of South Korea's targeted responses to the first large-scale COVID-19 cluster in Seoul. We find that foot traffic and retail sales decreased only within a 300 meter radius of the cluster and recovered to its pre-outbreak level after four weeks. The reductions appear to be driven by temporary business closures rather than the risk avoidance behavior of the citizens. Our results imply that less intense, but more targeted COVID-19 interventions, such as pin-pointed, temporary closures of businesses, can be a low-cost alternative after lifting strict social distancing measures.
Keywords: E2; H12; I12; I18; 330; COVID-19; pandemic; information disclosure; risk avoidance; foot traffic; retail sales; cell phone signal data; card transaction data